Product Ready to Use Therapeutic Food (RUTF) Use Combination of Green Pea and Peanut - Agustini, Ida Ayu Surya; Suter, I Ketut; Permana, I. Dw. G. Mayun (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 1 (2018): Scientific Journal of Food Technology, 2018)
The aim of this research is to make a formula of RUTF using combination of green pea and peanut as the base ingridients. By using this combination, it is expected that this product will have precise energy and protein content with good taste for children. Randomized block design was used and sensoric properties were analysed to get best formulation in term of nutrition content and sensoric properties. The eksperiment, there were ratio of peanut and green pea in that 6 formulations are 80:20,70:30,60:40,40;60,30:70, and 20:80. Data from statistical analysis showed that there is no significant difference in nutrition content and sensoric properties between 6 formulations (p>0.05). Selection of best formulation among these 6 formulations was done using effectitivity method. Using that method, RUTF which contains green pea and peanut with 6:4 ratio is the best product.